Islamic Eco-Theology in Practice: Revitalizing Environmental Stewardship and Tawhidic Principles in Agricultural Community - Afandi, Agus; Mardliyah, Sjafiatul; Ashfaq, Asia; Saud, Muhammad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article describes the development of environmentally friendly farming patterns through organik farming practices, sustainable pest control, the application of monotheistic values in agriculture, and the role of farmer groups as learning platforms. The research method employed is Participatory Action Research (PAR), involving collaboration with farmer groups and the community. The steps include in-depth research using Participatory Rural Appraisal (PRA), strategic planning, resource mobilization, and the development of critical awareness. The collaboration process includes experimenting with organik farming, analyzing agricultural conditions, seasonal calendars, power relations, and planning for environmentally friendly farming. Farmer groups learn from other organik farming communities, practicing the production of compost, liquid organik fertilizer, botanical pesticides, and land processing. The study of Agricultural Tawhid strengthens the spiritual dimension in farming. The outcomes include awareness of the importance of environmental conservation by reducing chemical usage, replacing them with natural materials, and developing skills in environmentally friendly farming practices. This awareness is grounded in the perspective that farming is an act of worship and a noble endeavor to provide sustenance for humans and other creatures.